Physical activity intensity, sedentary time, and body composition in preschoolers. - Collings, P; Brage, S; Ridgway, C; Harvey, N; Godfrey, K; Inskip, H; Cooper, C; Wareham, N; Ekelund, U (2013)
BACKGROUND: Detailed associations between physical activity (PA) subcomponents, sedentary time, and body composition in preschoolers remain unclear. OBJECTIVE: We examined the magnitude of associations between objectively measured PA subcomponents and sedentary time with body composition in 4-y-old children. DESIGN: We conducted a cross-sectional study in 398 preschool children recruited from the Southampton Women's Survey. PA was measured by using accelerometry, and body composition was measured by using dual-energy X-ray absorptiometry. Associations between light physical activity, moderate physical activity (MPA), vigorous physical activity (VPA), and moderate-to-vigorous physical activity (MVPA) intensity; sedentary time; and body composition were analyzed by using repeated-measures linear regression with adjustment for age, sex, birth weight, maternal education, maternal BMI, smoking during pregnancy, and sleep duration. Sedentary time and PA were also mutually adjusted for one another to determine whether they were independently related to adiposity. RESULTS: VPA was the only intensity of PA to exhibit strong inverse associations with both total adiposity [P < 0.001 for percentage of body fat and fat mass index (FMI)] and abdominal adiposity (P = 0.002 for trunk FMI). MVPA was inversely associated with total adiposity (P = 0.018 for percentage of body fat; P = 0.022 for FMI) but only because of the contribution of VPA, because MPA was unrelated to fatness (P ≥ 0.077). No associations were shown between the time spent sedentary and body composition (P ≥ 0.11). CONCLUSIONS: In preschoolers, the time spent in VPA is strongly and independently associated with lower adiposity. In contrast, the time spent sedentary and in low-to-moderate-intensity PA was unrelated to adiposity. These results indicate that efforts to challenge pediatric obesity may benefit from prioritizing VPA.